Local Treatment of Recent Arterial Thromboembolic Occlusions with Brinase - Nyman, D; da Silva, M. A; Widmer, L. K; Duckert, F (Thrombosis and Haemostasis, 1975)
Brinase was administered intra-arterially in 16 patients with thrombotic or embolic arterial occlusions. Angiography could be performed before and after treatment in 13 patients. Thrombolysis was obtained in 3 of 9 patients with thrombotic and in 3 of 4 patients with embolic occlusions. In 3 patients severe local side effects occurred.